Surprises in probability : seventeen short stories - Tijms, Henk (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
"This book bundles together a variety of probability applications through entertaining stories that will appeal to a broad readership. What are the best stopping rules for the dating problem, the Chow-Robbins game and the devil's penny game? How the gambler's fallacy created the Venice-53 hysteria in the national Italian lottery. These questions and many others are addressed in seventeen short chapters that can be read independently. The engaging stories are instructive as well and demonstrate valuable probabilistic ideas"--
What is casino credit worth? --
One hundred prisoners : freedom or death --
Birthday surprises and 500 Oldsmobiles --
Was the champions league rigged? --
Benford goes to the casino --
Surprising card games, or, it's all in the cards --
The lost boarding pass and the Seven Dwarfs --
Monte Carlo simulation and probability : the interface --
Lotto nonsense : the world is asking to be deceived --
March madness grips the USA --
Coincidences and impossibilities --
Gambler's fallacy --
Euler's number e is everywhere --
The 10 most beautiful formulas in probability --
Beating the odds on the lottery --
Investing and gambling with Kelly --
To stop or not to stop? That is the question.
Includes bibliographical references and index.
ESS
Parama
Keywords: Probabilities -- Popular works; Probabilities -- Problems, exercises, etc